2017
DOI: 10.1007/s00394-017-1399-x
|View full text |Cite
|
Sign up to set email alerts
|

The α’ subunit of β-conglycinin and various glycinin subunits of soy are not required to modulate hepatic lipid metabolism in rats

Abstract: Overall, soy protein deficient in the α' subunit of β-conglycinin and A1-5 subunits of glycinin maintain similar hypolipidemic function compared to the conventional soy protein. The exact bioactive component(s) warrant identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The results showed that soybean protein lacking the β-conglycinin α′ subunit and glycinin A1–5 subunit had similar lipid-lowering functions as conventional soybean protein, but the bioactive components in soybean responsible for the lowered lipid were not clear. 1 Research shows that the α + α′ subunit had higher LDL reception and its upregulation activity was higher than that of the β subunit. 9 Previous studies have shown that the effect of soybean 7S globulin subunits on the upregulation of LDL receptors in HepG2 cells confirms the effective roles of these subunits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that soybean protein lacking the β-conglycinin α′ subunit and glycinin A1–5 subunit had similar lipid-lowering functions as conventional soybean protein, but the bioactive components in soybean responsible for the lowered lipid were not clear. 1 Research shows that the α + α′ subunit had higher LDL reception and its upregulation activity was higher than that of the β subunit. 9 Previous studies have shown that the effect of soybean 7S globulin subunits on the upregulation of LDL receptors in HepG2 cells confirms the effective roles of these subunits.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, advancements in food science and processing technologies as well as changes in the health concepts of consumers have led to soy protein isolate (SPI) being widely used as a food processing raw material to increase nutritional value and improve product quality. [1][2][3][4] SPI is mainly composed of two proteins, β-conglycinin (7S) and glycinin (11S). 7S is a trimeric glycoprotein (150-200 kDa), mainly comprising α (72 kDa), α′ (76 kDa) and β (53 kDa) peptides.…”
Section: Introductionmentioning
confidence: 99%
“…β -conglycinin, one of the major storage proteins in soybean, was shown to reduce serum triglycerides, glucose and insulin levels [ 12 ], and prevented high-fat induced fatty liver in mice [ 59 ], and increased blood adiponectin level and insulin sensitivity in Wistar rats [ 23 ]. Our studies, using soy proteins with depletion of different subunits, further demonstrated that α ’ subunit of β -conglycinin and all acidic polypeptides (A1 to A5) in glycinin were not required for the lipid-lowering effects and fatty liver reduction of soy proteins [ 60 , 61 ]. This indicates that the other subunits of β -conglycinin and glycinin may play major roles in this regard.…”
Section: Introductionmentioning
confidence: 99%